The Effectiveness of Government Communication in Qatar and Its Impact on Public Satisfaction - Al-Otaibi, Zamel Badi (Journal of Ecohumanism, 2025)
This study aimed to evaluate the effectiveness of government communication in the State of Qatar from the public's perspective by exploring citizens' and residents' level of interaction with and satisfaction regarding the content and communication channels used by government entities on social media platforms. The study adopted a quantitative approach, collecting data from a simple random sample of 311 individuals using an electronic questionnaire that included measures to assess the characteristics of communication content and channels and the public's satisfaction level. The study found a moderate level of overall public satisfaction with current government communication, with variations in the evaluation of some aspects, such as the extent to which content focuses on public interests and the level of availability of interactive tools. The results also revealed a statistically significant positive effect of several characteristics of communication content (such as topic importance, visual appeal, and encouragement of interaction) and communication channel characteristics (such as meeting information needs, engagement, and platform diversity) on public satisfaction. These findings enrich scientific knowledge about this effectiveness's determinants and provide practical insights for improving its practices to serve the public interest.